KAJIAN KRITIS EFEKTIVITAS PENERAPAN GETTING PORTAL COMMITMENT SEBAGAI TEKNIK KOMUNIKASI PERSUASIF - Yusri Yusri (Jurnal Komunikasi dan Media, 2025)
Persuasive communication is a form of communication that focuses on influencing the attitudes, beliefs, and behavior of others to align with the communicator's goals without any element of coercion. Getting portal commitment is a technique that is beginning to receive attention in modern communication studies. It is a communication strategy for generating and binding a small initial commitment (portal commitment) from the recipient, which can then be developed into a larger commitment. This article discusses the concept, theory, implementation, and effectiveness of the getting portal commitment technique in various communication contexts, such as interpersonal, organizational, business, social and political communication. Literature reviews and case studies indicate that this technique is effective because it utilizes the principle of psychological consistency, which encourages individuals to adjust their behavior according to their abilities in accordance with the initial commitment they have made. However, this technique also contains an ethical dimension that must be considered to prevent it from turning into manipulation. This article is expected to contribute to the development of persuasive communication studies and offer practical strategies for communication practitioners.